The Influence of Brand Equity and Internet Banking Services on the Decision to Become a Customer of an Indonesian Islamic Bank - Saputri, Khana; Laurence, Calvin Audie; Winata, Frederick; Andrian Cuaca, Albert; Fauzi Rambe, Muis (Universitas Muhammadiyah Pontianak, 2026)
This study aims to analyze the effect of brand equity and internet banking service quality on the decision to become a customer of Bank Syariah Indonesia (BSI). This quantitative study involved 100 active users of BSI Internet Banking selected through simple random sampling. Data were analyzed using SEM-PLS with SmartPLS 4.0 software. The results show that brand equity (β = 0.476; p < 0.05) and internet banking service quality (β = 0.406; p < 0.05) have a positive and significant effect on the decision to become a BSI customer. The R-square value of 0.656 indicates that both variables explain 36% of customer decisions. These findings highlight the importance of strengthening brand value and improving digital banking service quality to increase customer decisions in Islamic banking institutions.